Liquid disaster and frigid response: Disaster and social exclusion. (September 2015) - Jha, Manish K
Based on the author's engagement with humanitarian response after massive floods in the Kosi region in Bihar, this article highlights that the disaster caused by floods is not an accidental interruption but is linked to the socio-political structure of the state. Through an examination of the processes of social exclusion in times of disaster, the article situates the role of state and society in the context of recent floods. This article deals with the discrimination and exclusion of weaker sections of the society during rescue, relief and rehabilitation process. Individual and communities' powerlessness, as was encountered immediately after floods, were put in the perspective of the structural situation in the region.